Statistical Data Board on Mathematical Problem-Solving - Fatimah, Neneng; Suryadi, Didi (International Conference on Elementary Education, 2021)
The ability of mathematical problem-solving is a required ability for students in solving mathematical problems, other academic problems, or even daily life. This research is motivated by a lack of primary school students’ problem-solving ability. The research was conducted to investigate the influence of statistical data board learning media on the mathematical problem-solving ability on data processing material for fourth-grade students in primary school. This research employed a quantitative approach by involving 73 fourth-grade students in one of the primary schools in Sumedang Regency as the research subjects and analyzing the data using a t-test. The research results revealed that the significance value obtained by the students was < 0.05. Therefore, it indicated that statistical data board learning media had an influence on mathematical problem-solving on data processing material.